ANALISIS PENDAPATAN “TOMAT CERI’’ TEKNIK HIDROPONIK USAHA URBAN HYDROFARM DI BATU KOTA KECAMATAN MALALAYANG KOTA MANADO - Nehemia Nafthalia Paoki; Noortje Marsellanie Benu; Ellen Grace Tangkere (Sam Ratulangi University, 2021)
The purpose of this study was to analyze the Revenue of â€œCherry Tomatoesâ€ in the Urban Hydrofarm Business Hydroponic Technique in Batu Kota, Malalayang District, Manado City. Quantitative data analysis method to determine the income of â€œCherry Tomatoesâ€ Hydroponic Engineering Business Urban Hydrofarm. The data used in this study are primary data and secondary data. Primary data was obtained through interviews with the help of a list of previously prepared questions. Secondary data were obtained from books, internet, journals, and other sources related to the problems discussed in this study. The results showed that the total revenue from the â€œCherry Tomatoâ€ Urban Hydrofarm business was Rp. 8.600,000. While the total cost incurred in the production process of cherry tomatoes during the 6-month planting period is Rp. 6.234.200. So that the Urban Hydrofarm business hydroponic technique â€œCherry Tomatoesâ€ obtained in Batu Kota, Malalayang District, Manado City, is Rp. 2.365.800, during 5x harvest / 6 planting period.